Controlled Adhesion of Ice—Toward Ultraclean 2D Materials. Issue 14 (25th February 2023) - Liu, Haijun; Thi, Quoc Huy; Man, Ping; Chen, Xin; Chen, Tianren; Wong, Lok Wing; Jiang, Shan; Huang, Lingli; Yang, Tiefeng; Leung, Ka Ho; Leung, Tsz Tung; Gao, Shan; et al.
Abstract: The scalable 2D device fabrication and integration demand either the large‐area synthesis or the post‐synthesis transfer of 2D layers. While the direct synthesis of 2D materials on most targeted surfaces remains challenging, the transfer approach from the growth substrate onto the targeted surfaces offers an alternative pathway for applications and integrations. However, the current transfer techniques for 2D materials predominantly involve polymers and organic solvents, which are liable to contaminate or deform the ultrasensitive atomic layers. Here, novel ice‐aided transfer and ice‐stamp transfer methods are developed, in which water (ice) is the only medium in the entire process. In practice, the adhesion between various 2D materials and ice can be well controlled by temperature. Through such controlled adhesion of ice, it is shown that the new transfer methods can yield ultrahigh quality and exceptional cleanliness in transferred 2D flakes and continuous 2D films, and are applicable for a wide range of substrates. Furthermore, beyond transfer, ice can also be used for cleaning the surfaces of 2D materials at higher temperatures. These novel techniques can enable unprecedented ultraclean 2D materials surfaces and performances, and will contribute to the upcoming technological revolutions associated with 2D materials. Abstract : Novel ice‐aided transfer, ice‐stamp transfer, and ice cleaning methods, completely free from polymer and solvents, are developed to yield ultrahigh quality and exceptional cleanliness in 2D materials, which will contribute to technological revolutions in 2D materials, and their associated structures and devices.